Can pyroptosis be a new target in rheumatoid arthritis treatment? - Wu, Dengqiang; Li, Yujie; Xu, Ranxing (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune disease of undefined etiology, with persistent synovial inflammation and destruction of articular cartilage and bone. Current clinical drugs for RA mainly include non-steroidal anti-inflammatory drugs( NSAIDs), glucocorticoids, disease modifying anti-rheumatic drugs (DMARDs) and so on, which can relieve patients' joint symptoms. If we want to have a complete cure for RA, there are still some limitations of these drugs. Therefore, we need to explore new mechanisms of RA to prevent and treat RA radically. Pyroptosis is a newly discovered programmed cell death(PCD) in recent years, which is characterized by the appearance of holes in cell membranes, cell swelling and rupture, and the release of intracellular pro-inflammatory factors into the extracellular space, resulting in a strong inflammatory response. The nature of pyroptosis is pro-inflammatory, and whether it is participating in the development of RA has attracted a wide interest among scholars. This review describes the discovery and mechanism of pyroptosis, the main therapeutic strategies for RA, and the role of pyroptosis in the mechanism of RA development. From the perspective of pyroptosis, the study of new mechanisms of RA may provide a potential target for the treatment of RA and the development of new drugs in the clinics.